2020
DOI: 10.1016/j.energy.2020.118046
|View full text |Cite
|
Sign up to set email alerts
|

Fuel cells as combined heat and power systems in commercial buildings: A case study in the food-retail sector

Abstract: This work investigates the viability of fuel cells (FC) used as combined heat and power systems (CHPs) in commercial buildings with a specific focus on supermarkets. Up-to-date technical data from a fuel cell manufacturing company was obtained and applied to evaluate their viability in an existing food-retail building. A detailed optimisation model described in previous works enhancing distributed energy system management is expanded upon to optimise the techno-economic performance of FC-CHP systems. The optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Nonetheless, green CPPAs can carry high risks as guaranteeing the supply of power at a reasonable cost might prove difficult and deter organisations away from them [8]. As an alternative to green CPPAs, if organisations can allow it in their premises producing energy on-site through distributed technologies is another viable option to decarbonise operations in energy intensive buildings, that is if the economic case can be justified [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, green CPPAs can carry high risks as guaranteeing the supply of power at a reasonable cost might prove difficult and deter organisations away from them [8]. As an alternative to green CPPAs, if organisations can allow it in their premises producing energy on-site through distributed technologies is another viable option to decarbonise operations in energy intensive buildings, that is if the economic case can be justified [9].…”
Section: Introductionmentioning
confidence: 99%
“…Salvador Acha et al investigated the feasibility of a 460 kW PAFC-based CHP system in the application of a commercial building. The results indicated that the FC-CHP system is financially competitive against the internal combustion engine [22]. From the above literature, for the analysis of the operating and economic performance of a fuel-cell-based CHP system, relatively accurate load data plays a vital role, as the CHP performance is highly dependent on the load matching condition.…”
Section: Introductionmentioning
confidence: 99%
“…The value of calculating today's and tomorrow's electricity costs with HH granularity can provide very valuable insights to the academic and industrial communities interested in conducting techno-economic analysis of investments in the built environment. For example, the authors of this work have employed the MUKERC data to assess the optimal design and operation of distributed technologies for commercial buildings such as: combined-heat and power systems [38], photo-voltaic and battery systems [39], ORC engines [40], and fuel cell CHP systems [41]. Similarly, as the shift towards the electrification of heating takes place the added-value of conducting bespoke analysis of technologies displacing fossil fuels with specific electricity cost data for a specific building can give clarity to decision-makers.…”
Section: Application Of the Mukerc Framework In The Literaturementioning
confidence: 99%